Standard development at the Human Variome Project - Smith, Timothy D. (Database (Oxford), 2015)
The Human Variome Project (HVP) is a world organization working towards facilitating the collection, curation, interpretation and free and open sharing of genetic variation information. A key component of HVP activities is the development of standards and guidelines. HVP Standards are systems, procedures and technologies that the HVP Consortium has determined must be used by HVP-affiliated data sharing infrastructure and should be used by the broader community. HVP guidelines are considered to be beneficial for HVP affiliated data sharing infrastructure and the broader community to adopt. The HVP also maintains a process for assessing systems, processes and tools that implement HVP Standards and Guidelines. Recommended System Status is an accreditation process designed to encourage the adoption of HVP Standards and Guidelines. Here, we describe the HVP standards development process and discuss the accepted standards, guidelines and recommended systems as well as those under acceptance. Certain HVP Standards and Guidelines are already widely adopted by the community and there are committed users for the others.